Släpslangspridning av gödsel, kan det löna sig? - Johansson, Niklas (2005)
I have chosen to work with drag hose system and try to find an alternative to spread manure with a usually tank system, see if you can make a profit and what advantage and disadvantage the system has. The purpose whith the project has been to try to make a system that can spread manure at better occasions than farmers do today and above everything make a financial addition. Today it is just a heavy work and takes a lot of time. I have counted on investment costs and carefully examined what equipment you need. I have not the technical details in my project, I have just tried to understand how it is to spread manure with drag hose system today. What is drag hose system? You put a hose in your manuretank, connect it to a pump that is driven by a traktor or stationary engine. You place a hose that reach the field were you are going to spread. You connect a special hose that you drag to the field. On the tractor is a hoseramp fitted, 12 meters wide. The cost to invest in drag hose system is about two million Swedish crowns. Then you get machinery that can be used by both contractors and by farmers. The drag hose system is more expensive to buy than a system with tank but you get higher capacity and you don't have the pressure on the soil, and you also can drive when the fields are wet which is a big benefit when you get wet years. The system is a little bit more complicated then to drive with tank. You have to make a plan of how to drive because you have the hose to look up with. The system is new in Sweden, about 25 systems are in use today. I think that we are going to see more of the system in the future because the farms is getting bigger and more manure should be spread on shorter time.